STRATEGI KEPALA SEKOLAH DALAM UPAYA PENGADAAN SARANA DAN PRASARANA PENDIDIKAN DI SMKN 5 KOLAKA TIMUR - Iksan Sani; Suhrah; Hartono (Universitas Sains Islam Al Mawaddah Warrahmah Kolaka, 2025)
Strategy in procurement of educational facilities and infrastructure is a series of planned and systematic actions taken to meet the needs of facilities and equipment that support the learning process in educational institutions. This strategy is important to ensure the availability of a conducive, effective and efficient learning environment. As done by the principal of SMKN 5 Kolaka Timur who implemented several strategies in meeting school needs are as follows: a. Use of committee funds Procurement of educational facilities and infrastructure is a crucial step in improving the quality of learning. However, this process is often faced with various challenges, such as budget constraints and complicated bureaucracy